New record of the genus Zethus Fabricius from Taiwan, with the description of Z. taiwanus sp. nov. and a key to the species of trimaculatus-group (Hymenoptera: Vespidae: Eumeninae) - Yeh, Wen-Chi; Lu, Sheng-Shan (Zootaxa, 2017)
The authors report the genus Zethus Fabricius from Taiwan for the first time and describe a new species, Zethus taiwanus sp. nov. (holotype, Guishan, Xindian District, New Taipei City), which is most similar to Z. nigerrimus Gusenleitner, 2001 in female morphology. Zethus trimaculatus Cameron, 1904 is re-described based on the female holotype and the male of Z. nigerrimus also described for the first time. Following Giordani Soika’s criteria for sub-groupings of the Oriental Zethus, Z. taiwanus, Z. nigerrimus and two recently described species, Z. tansoneus Nguyen & Carpenter, 2016 and Z. tumidus Nguyen & Carpenter, 2016, are subsequently added to the trimaculatus-group. A key to the Zethus trimaculatus-group is provided based mainly on male characters.